PENGEMBANGAN POP UP BOOK BERBASIS KARAKTER NASIONALISME SEBAGAI UPAYA MENINGKATKAN LITERASI SISWA SD - Yusinta Dwi Ariyani; Susi Setyowati (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2021)
This study aims to determine the feasibility and effectiveness of pop up books based on nationalism characters to improve literacy of second grade elementary school students. The research model used is the research and development model of Borg & Gall (1983: 775-776). Assessment of teaching material products that have been filled in by media experts, the final criteria from the aspects obtained are based on the results of the conversion of quantitative data into a value on a scale of 5, The number of assessments from validation conducted by media experts is 38, then the results of the assessment from media experts are in the range score X> 33.54 which overall the result is very good. While the results of discussions with class II teachers at SD NU Ma'arif Nurul Jannah Kulon Progo, the final criteria from the aspects obtained are based on the results of the conversion of quantitative data into a value on a scale of 5, the number of assessments made by the teacher is 72, then the results of the teacher's assessment are in the range of scores X> 63 which overall the results are very good. Based on the independent sample t-test, it shows that the t value is equal to -18.256. Meanwhile, the t table value on df is equal to 10 and Î± of 0.05 (sig.2-tailed) shows that the t table value is Â± 2,160. This value is much greater than the calculated t value. So it can be concluded that ho is rejected. This means that the posttest scores of the experimental class and the control class from the operational field test results provide a significant difference. The Pop Up Book developed is said to be effective because there are significant differences between the control class and the experimental class.